Advances in Studies on the Pharmacological Activities of Fucoxanthin - Han Xiao; Jiarui Zhao; Chang Fang; Qi Cao; Maochen Xing; Xia Li; Junfeng Hou; Aiguo Ji; Shuliang Song (Marine Drugs, 2020)
Fucoxanthin is a natural carotenoid derived mostly from many species of marine brown algae. It is characterized by small molecular weight, is chemically active, can be easily oxidized, and has diverse biological activities, thus protecting cell components from ROS. Fucoxanthin inhibits the proliferation of a variety of cancer cells, promotes weight loss, acts as an antioxidant and anti-inflammatory agent, interacts with the intestinal flora to protect intestinal health, prevents organ fibrosis, and exerts a multitude of other beneficial effects. Thus, fucoxanthin has a wide range of applications and broad prospects. This review focuses primarily on the latest progress in research on its pharmacological activity and underlying mechanisms.